2021
DOI: 10.1088/1742-6596/1764/1/012103
|View full text |Cite
|
Sign up to set email alerts
|

Need Analysis for Development of Web-Based Flipped Classroom Learning Models in Vocational Education

Abstract: This study aims to determine the potential and needs of lecturers and students in studying computer network security which will be used as a basis for developing a web-based inverted classroom model in vocational education. This research is also based on 21st century learning competencies needed in the digital age such as critical thinking, communication, collaboration and creativity. This research needs analysis consists of field observations and literature studies. This research is a type of descriptive rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
4
0
1
Order By: Relevance
“…Researchers agree that media literacy is a basic competence necessary for the younger generation to grow up in today's digital world [15], which will help to form an information culture and immunity to the destructive potential of the Internet environment and its poorquality content [16], as well as maximize the opportunities to use digital media. Most studies emphasize the leading role of cognitive competencies in the structure of media literacy, referring to the development of critical thinking in relation to a variety of digital content [67]. However, the role of technological, social, sociocultural and ethical components [74], and their optimal combination cannot be underestimated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers agree that media literacy is a basic competence necessary for the younger generation to grow up in today's digital world [15], which will help to form an information culture and immunity to the destructive potential of the Internet environment and its poorquality content [16], as well as maximize the opportunities to use digital media. Most studies emphasize the leading role of cognitive competencies in the structure of media literacy, referring to the development of critical thinking in relation to a variety of digital content [67]. However, the role of technological, social, sociocultural and ethical components [74], and their optimal combination cannot be underestimated.…”
Section: Discussionmentioning
confidence: 99%
“…Thai found that a quarter of media literacy studies do not even include a definition of the term [66], while the remaining three quarters cover a wide range of definitions, with about half providing their own definition. Most scholars agree that media literacy focuses on specific knowledge and skills that can support critical understanding and use of media [67]. Most researchers indicate that critical thinking is a basic skill included in the general competency of media literacy [68].…”
Section: Contemporary Principles and Educational Solutions For Teachi...mentioning
confidence: 99%
“…Las estrategias metodológicas con mayor asociación a lograr este tipo de competencias son el aprendizaje basado en proyectos [37], [72]- [78], el aprendizaje basado en desafíos , aunque otros como el aula invertida [79], [80], también son recomendaciones encontradas en la literatura.…”
Section: A Innovación Y Emprendimiento (Irc Innovation-related Compet...unclassified
“…This subject aims for each student to understand and practice material ranging from the concept of computer networks to being able to design a topology, perform IP subnetting calculations and also be able to operate the network to be interconnected using devices such as routers, switches, and computers. Based on preliminary analysis and relevant research conducted, some problems are often faced in learning Computer Network courses, namely limited practice time in computer laboratories (Bradley & Kendall, 2014;Efendi et al, 2021;Efendi & Ali, 2019;Segec et al, 2019). In this subject, students must gain practical experience configuring and operating computer networks.…”
Section: Introductionmentioning
confidence: 99%